OPTIMASI CMC-Na DAN KARBOMER SEBAGAI PENGIKAT PADA FORMULA PASTA GIGI TRIKLOSAN SECARA SLD - Elya Zulfa; Fajar Indah; Mimiek Murukmihadi (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2017)
ABSTRACT CMC-Na is a hydrogel binding agent that can absorb water and carbomer. This excipient is single phase system that does not absorb but swell in the water. Extrudability, cohesiveness, and the active substance dispersed well in the mouth is an important function of the binding agent. The purpose of this study is to find the optimum formula triclosan toothpaste with a combination CMC-Na and carbomer as a binding agent. The formula was obtained based on Design Expert® 9.0.3 was, F1 (5.50%:0.50%); F2 (4.75%:1.25%); F3 (4.75%:1.25%); F4 (5.50%:0.50%); F5 (4.00%:2.00%); F6 (4.38%:1.63%); F7 (4.00%:2.00%) and F8 (5.13%:0.88%). Viscosity, pH, and the level of preference considered to decide the optimum formula. The Equations was obtained based on experiments and theoretical verified using One Sample T-test at 95% confidence level. Based on Simplex Lattice Design equation, the proportion CMC-Na:carbomer is 5.35%:0.65% shown the optimum formula. Experimental and theoretical results have the same response (p>0.05). The combination of CMC-Na and carbomer affects the physical characteristics and level of preference, which increased pH, reduces viscosity and increase the level of preference. Key words: Optimation, toothpaste formula, binding agent, CMC-Na, carbomer